Stable and Variable Parts of Microbial Community in Siberian Deep Subsurface Thermal Aquifer System Revealed in a Long-Term Monitoring Study - Frank, Yulia A.; Kadnikov, Vitaly V.; Gavrilov, Sergey N.; Banks, David; Gerasimchuk, Anna L.; Podosokorskaya, Olga A.; Merkel, Alexander Y.; Chernyh, Nikolai A.; Mardanov, Andrey V.; Ravin, Nikolai V.; Karnachuk, Olga V.; Bonch-Osmolovskaya, Elizaveta A. (Frontiers in Microbiology, 2016)
The goal of this work was to study the diversity of microorganisms inhabiting a deep subsurface aquifer system in order to understand their functional roles and interspecies relations formed in the course of buried organic matter degradation. A microbial community of a deep subsurface thermal aquifer in the Tomsk Region, Western Siberia was monitored over the course of five years via a 2.7 km deep borehole 3P, drilled down to a Palaeozoic basement. The borehole water discharges with a temperature of ca. 50oC. Its chemical composition varies, but it steadily contains acetate, propionate, and traces of hydrocarbons and gives rise to microbial mats along the surface flow. Community analysis by PCR-DGGE 16S rRNA genes profiling, repeatedly performed within five years, revealed several dominating phylotypes consistently found in the borehole water, and highly variable diversity of prokaryotes, brought to the surface with the borehole outflow. The major planktonic components of the microbial community were Desulfovirgula thermocuniculi and Methanothermobacter spp. The composition of the minor part of the community was unstable, and molecular analysis did not reveal any regularity in its variations, except some predominance of uncultured Firmicutes. Batch cultures with complex organic substrates inoculated with water samples were set in order to enrich prokaryotes from the variable part of the community. PCR-DGGE analysis of these enrichments yielded uncultured Firmicutes, Chloroflexi, and Ignavibacteriae. A continuous-flow microaerophilic enrichment culture with a water sample amended with acetate contained Hydrogenophilus thermoluteolus, which was previously detected in the microbial mat developing at the outflow of the borehole. Cultivation results allowed us to assume that variable components of the 3P well community are hydrolytic organotrophs, degrading buried biopolymers, while the constant planktonic components of the community degrade dissolved fermentation products to methane and CO2, possibly via interspecies hydrogen transfer. Occasional washout of minor community components capable of oxygen respiration leads to the development of microbial mats at the outflow of the borehole where residual dissolved fermentation products are aerobically oxidized. Long-term community analysis with the combination of molecular and cultivation techniques allowed us to characterize stable and variable parts of the community and propose their environmental roles.